SIMULATION OF LINEAR POSITION HYDRAULIC DRIVE FOR MACHINE POWER DRILL FEED - Valentin Sergeyevich Sidorenko; Le Trung Kien (Advanced Engineering Research, 2013)
The generalized trajectory of the power drill (PD) operational cycle is considered. In the case under study, the PD shows the increased speed and positioning accuracy of the fluid-feed. An automated hydraulic drive for providing the structural parametric control over the operational cycle and PD positioning is offered. A generalized mathematical model of the PD feed drive dynamic system is presented. The simulation experiment has permitted to determine kinematic and dynamic characteristics of the tool-feeding drive under the metering-out control. The cutting feed rate effect on the tool positioning accuracy under the deceleration and at the end of processing is determined. This allows forming time-optimal and ideal for positioning accuracy cycles under the field processing conditions.